Uncommon Neonatal Hemi-Diaphragmatic Paralysis: Case Reports and Literature Review - Carlhan-Ledermann, Audrey; Olela, Otis; Pfister, Riccardo E; Hanquinet, Sylviane; Munoz, Francisca Barcos (Archives of Clinical and Biomedical Research, 2022)
Background: Diaphragmatic paralysis (DP) is a rare cause of respiratory distress in newborns with potentially severe outcome. Two cases illustrate the clinical presentation, etiology, evaluation, treatment, and outcome of diaphragmatic paralysis in newborn. Cases presentation: First, a 890 g male preterm of 26 weeks who developed a left DP after pleural drain placement and completely recovered within 6 to 9 months without surgery. The second case, a female neonate born at 38 1/7 weeks of gestation, developed a right DP secondary to obstetrical trauma with associated Erb’s palsy and completely recovered spontaneously within one week. Conclusions: Diaphragmatic paralysis is a rare but potentially life-threatening condition in newborns. Indications and timing for surgical or conservative treatment remain controversial. DP management should be addressed in a multidisciplinary manner. With optimized respiratory and feeding management, spontaneous favorable outcomes may be expected, avoiding long-term complications of a surgical plication, but require concerted expectant management and considerable time. Our cases encourage supportive expectant management.